Factors limiting cattle productivity in highland areas of Nigeria. II. (Report on second phase of project carried out from January 1978 to July 1980) - Synge, B.A. (1980)
Reports on factors affecting productivity of White Fulani cattle on Jos Plateau, Nigeria. Topical discussions on calving rate and interval, birth and monthly live weights, milk yield and composition, diseases, nutrition, purchases and exchanges were examined in 23 White Fulani cattle herds. Information on the economics of overcoming constraints like malnutrition through supplementary feeding with cotton seed cake and control of facioliasis and parasitic gastroenteritis included. Results of surveys on herd structure, size, livestock and human population in the area are given.